Optimasi Electrical Submersible Pump (ESP) Pada Sumur MFR-21 Berdasarkan Keadaan Sumur di Masa Depan - Abdi Suprayitno; Muhammad Fauzi Ramadhan; Rohima Sera Afifah (Universitas Proklamasi 45, 2024)
When wells are produced continuously, the reservoir pressure will continue to decrease resulting in decreased production performance from the well. To optimally increase the rate of production, optimization is carried out using an Artificial Lift Electrical Submersible Pump. Based on data from the journal,